Repensando la Política Nacional para la Transversalización del Enfoque Intercultural - Gómez Garay, Lucía de Fátima (2021)
This presentation aims to put into perspective and rethink the different aspects of the “Política Nacional para la Transversalización del Enfoque Intercultural” [National Policy for the Transversality of the Intercultural Approach], as well as its relevance according to the current problems of Peruvian society. Thus, it will be structured as follows: first, we will present the antecedents and the social and political context in which this policy arises, in addition to the current context in which this policy must unfold. Second, we will review the different concepts used in this presentation, establishing their respective connotations, differences and difficulties. Therefore, we will examinate the terms “interculturality”, “intercultural approach” and “transversality” to understand the meaning (or meanings) of this national policy. Third, the structure of this policy will be analyzed according to its approaches and scope, as well as the legal framework and the actors responsible for its execution. Lastly, we will observe the challenges in relation to our current context, as well as a deeper analysis of the tensions that arise between those reflected in the politics and reality of the country, such as the recognition of cultural diversity, social inclusion and discrimination.